Factors Influencing Consumer Purchasing Behaviour Towards Purchase of Palm Leaf Craft. Issue 15 (23rd November 2022) - Krishnaraj, G.; Elangovan, N.; Prakash, C.
ABSTRACT: The handicraft sector plays a significant role in providing employment opportunities in rural and semi-urban areas of the country. It helps in generating substantial income for the artisans. The uses for palm leaves are abundant. Attractive items made of Palm Leaves are very popular in South India, mostly in Southern Andhra Pradesh and Tamil Nadu. However, to generate sustainable revenue through their products, the artisans need to understand the buyer's requirements. This study aims to understand the consumer's purchasing behavior when buying palm leaf products. The sample consists of 233 consumers with diverse backgrounds from the state of Tamil Nadu, India. A questionnaire was developed to measure awareness and attitude influence while purchasing palm leaf products. The results can help the artisans to get an insight into end-user expectations and requirements toward palm leaf products and suggest strategies to increase the income of artisans.